METHODS EVALUATION AND OF MECHANISM FOR SELECTING MODERN MANAGING PERSONNEL IN THE EDUCATION SYSTEM - Khurramov Sanjar Ravshanovich (International Journal on Orange Technologies, 2020)
Today, provision of the state institutions, including the education system with highly qualified personnel, is one of the priority directions of the country's policy. Personnel capacity is one of the key factors in improving the efficiency of the organization's goals and objectives, liberalization of all spheres, and implementation of key tasks before society and the state in the process of reforms. Therefore, a mechanism has been created to select the most suitable candidates for management in the education system